A comparison of models for ductile fracture prediction in forging processes - Cai Zheng (2007)
The possibility of predicting ductile fracture plays an important role in the design of components by forging processes. Experimental observations showed that the nucleation, growth and coalescence of voids are the mechanisms that control the initiation and propagation of fracture and that these mechanisms are influenced in different ways by factors like the hydrostatic stress, the equivalent stress or by the maximal principal stress. Many ductile fracture indicators, based on some or all of those factors, are available and used in many practical situations in the design of those components. In this work a comparative work of many of those criteria was undertaken. Different criteria were chosen amongst the more popular ones and from different groups, in which they may be classified, namely those based on micromechanics and those based on the geometry of voids or their growth mechanisms. The criteria based on the Continuous Damage Mechanics, in which a coupling between plastic deformation and material degradation is taken into account and that include different damage evolution descriptions for traction or compressive stress states, give a more correct and clear localization for the fracture initiation site.